Real-world listening effort in adult cochlear implant users - Perea Perez, Francisca (2023)
Cochlear implants (CI) are a treatment to provide a sense of hearing to individuals with severe-to-profound sensorineural hearing loss. Even when optimal levels of intelligibility are achieved after cochlear implantation, many CI users complain about the effort required to understand speech in everyday life contexts. This sustained mental exertion, commonly known as “listening effort”, could negatively affect their lives, especially regarding communication, participation, and long-term cognitive health.